PERAN PRAKTIK AKUNTANSI MANAJEMEN DALAM MENINGKATKAN EFISIENSI OPERASIONAL DAN KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR - Sirait, Siska Aminarti; J.E.Angelika Br.Nababan; Jhon Cristmas Damanik; Lira Setia Rajagukguk (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to examine the role of management accounting practices in improving operational efficiency and financial performance in manufacturing companies. In an increasingly competitive market environment, companies are required to implement effective cost control systems and performance reporting mechanisms. This research employs a literature review approach by analyzing various academic sources relevant to the topic. The findings indicate that management accounting techniques—such as budgeting, modern costing systems, and variance analysis—play a crucial role in identifying inefficiencies and optimizing decision-making processes. Moreover, management accounting supports financial transparency and helps reduce real earnings management practices, thereby enhancing the credibility of financial reporting. However, the implementation of management accounting still faces several challenges, especially in developing countries, such as limited human resource capacity, low integration of information systems, and insufficient managerial commitment. This study recommends strengthening internal competencies, developing integrated information technology infrastructure, and encouraging collaboration between industry and academia to formulate adaptive and sustainable management accounting strategies.